INVESTIGATING THE ASSOCIATION BETWEEN INTERPROFESSIONAL TRUST AND PATIENT SAFETY OUTCOMES IN PHARMACY AND NURSING TECHNICIAN COLLABORATIONS - Manahil Mubarak Daghim Al-Dhafiri, Bashayer Mubarak Daghim Al-Dhafiri, Muna Salem A Alanazi, RADHI Malouh S Aldhafeeri, salah aubayd aleanzi, Nouf Rumayd Raja Aldhafeeri, Nadiyah Eidan Shuraya Aldhafeeri, Amal Eidan Shuraya Aldhafeeri; Khalid Mohammed Khalaf Alharbi (Chelonian Research Foundation, 2022)
Interprofessional trust is a crucial component of effective collaboration among healthcare professionals, particularly in the context of pharmacy and nursing technician teams. This study aims to investigate the association between interprofessional trust and patient safety outcomes in collaborations between pharmacy and nursing technicians. A mixed-methods approach, involving surveys and semi-structured interviews, was employed to gather data from pharmacy and nursing technicians working in various healthcare settings. The findings reveal a significant positive correlation between interprofessional trust and patient safety outcomes, such as reduced medication errors and improved patient satisfaction. Key factors contributing to the development of interprofessional trust include open communication, shared decision-making, and clear role definitions. Barriers to trust, such as power imbalances and lack of understanding of each other's roles, are also discussed. The study highlights the importance of fostering interprofessional trust through targeted interventions, such as interprofessional education and team-building activities, to enhance patient safety outcomes in pharmacy and nursing technician collaborations. Keywords: interprofessional trust, patient safety outcomes, pharmacy technicians, nursing technicians, collaboration